Clinical implementation of 3D printing in the construction of patient specific bolus for electron beam radiotherapy for non-melanoma skin cancer. Issue 1 (October 2016) - Canters, Richard A.; Lips, Irene M.; Wendling, Markus; Kusters, Martijn; van Zeeland, Marianne; Gerritsen, Rianne M.; Poortmans, Philip; Verhoef, Cornelia G.
Abstract: Background and purpose: Creating an individualized tissue equivalent material build-up (i.e. bolus) for electron beam radiation therapy is complex and highly labour-intensive. We implemented a new clinical workflow in which 3D printing technology is used to create the bolus. Material and methods: A patient-specific bolus is designed in the treatment planning system (TPS) and a shell around it is created in the TPS. The shell is printed and subsequently filled with silicone rubber to make the bolus. Before clinical implementation we performed a planning study with 11 patients to evaluate the difference in tumour coverage between the designed 3D-print bolus and the clinically delivered plan with manually created bolus. For the first 15 clinical patients a second CT scan with the 3D-print bolus was performed to verify the geometrical accuracy. Results: The planning study showed that the V85% of the CTV was on average 97% (3D-print) vs 88% (conventional). Geometric comparison of the 3D-print bolus to the originally contoured bolus showed a high similarity (DSC = 0.89). The dose distributions on the second CT scan with the 3D print bolus in position showed only small differences in comparison to the original planning CT scan. Conclusions: The implemented workflow is feasible, patient friendly, safe, and results in high quality dose distributions. This new technique increases time efficiency.